2012
DOI: 10.1111/j.1365-2915.2012.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of bloodmeals and species composition in Culicoides biting midges

Abstract: Investigations of host preferences in haematophagous insects, including Culicoides biting midges (Diptera: Ceratopogonidae), are critical in order to assess transmission routes of vector-borne diseases. In this study, we collected and morphologically identified 164 blood-engorged Culicoides females caught in both light traps and permanent 12-m high suction traps during 2008-2010 in Sweden. Molecular analysis of the mitochondrial cytochrome c oxidase subunit I (COI) gene in the biting midges was performed to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 41 publications
(67 reference statements)
5
72
1
Order By: Relevance
“…Blood-feeding of Culicoides on pledglets was also demonstrated to underestimate rates of susceptibility to infection, as found previously with BTV [30,31]. The sequencing of the DNA barcode region (658 bp) of the cox1 gene for 67 individuals putatively identified as C. obsoletus from a single site in the UK provides potential evidence of cryptic diversity, however, how this relates to the morphologically cryptic species previously described in the Netherlands, Sweden and Switzerland [27][28][29]59] remains unclear.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Blood-feeding of Culicoides on pledglets was also demonstrated to underestimate rates of susceptibility to infection, as found previously with BTV [30,31]. The sequencing of the DNA barcode region (658 bp) of the cox1 gene for 67 individuals putatively identified as C. obsoletus from a single site in the UK provides potential evidence of cryptic diversity, however, how this relates to the morphologically cryptic species previously described in the Netherlands, Sweden and Switzerland [27][28][29]59] remains unclear.…”
Section: Discussionmentioning
confidence: 80%
“…Until recently four species within this subgenus have been identified within this region and are commonly referred to as the Obsoletus group, despite a lack of monophyly: Culicoides obsoletus (Meigen) and Culicoides scoticus Downes & Kettle; Culicoides dewulfi Goetghebuer and Culicoides chiopterus (Meigen) [24][25][26]. Several additional cryptic species have also recently been proposed whose taxonomic status, prevalence, abundance and involvement in transmission of arboviruses remains uncertain [27][28][29]. To date, these cryptic species have not been identified in the UK, despite a study that examined 79 individuals of the subgenus Avaritia using a 472 bp region of the mitochondrial cytochrome c oxidase subunit 1 gene (cox1) across ten geographically disparate sampling points [25].…”
Section: Introductionmentioning
confidence: 99%
“…While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011). Ninio et al (2011) identified the blood of horse, rabbit, pig, sheep and human in the abdomens of blood-fed C. obsoletus females, whereas Pettersson et al (2013) observed the blood of sheep, cattle and horse. This species, thus, seems to feed on a wide range of mammals (Lassen et al, 2012) but to prefer cattle, even when other hosts are present in adjacent areas (Bartsch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified the origin of blood present in the abdomen of adult females that have recently fed -which represent a very small proportion of any collection (Service, 1969) -to determine the host range (Blackwell et al, 1994;Bartsch et al, 2009;Garros et al, 2011;Lassen et al, 2011Lassen et al, , 2012Ninio et al, 2011;Calvo et al, 2012;Martinez-de la Puente et al, 2012;Pettersson et al, 2013). Other researchers have collected Culicoides adult females directly from animals used as bait, predominantly with sticky traps or by aspiration (Viennet et al, , 2013Ayllón et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that some Culicoides spp. have ornithophilic food preferences (Martínez-De La Puente et al 2011, Pettersson et al 2012, Santiago-Alarcon et al 2012. According to these publications, the Bulgarian list of species includes five species feeding on birds (Appendix 1).…”
Section: Discussionmentioning
confidence: 99%